Types of Tax Collection in the Indonesian Taxation System and Their Impact on Taxpayers - Audrey Aisyah Putri; Salsabilla Hamdi; Siti Rahayu; Zaldy Ichsan; Agil Fadhlur Rahman Dzaky Ramadhan (ISNU Sumatera Utara, 2025)
The tax collection system in Indonesia plays a crucial role in determining the effectiveness of state revenue and the level of taxpayer compliance. Three types of tax collection systems are used: the official assessment system, the withholding system, and the self-assessment system. The official assessment system directly determines the amount of tax payable, while the withholding system involves a third party withholding and remitting tax on behalf of the taxpayer. The self-assessment system empowers taxpayers to calculate, pay, and report their own taxes. This study aims to analyze the differences in the characteristics of these three systems and evaluate their impact on taxpayer behavior. The method used is a qualitative descriptive approach through literature review. The results show that the self-assessment system encourages independence and tax awareness, but presents challenges in oversight. The withholding system is considered effective in ensuring tax revenue, but still poses the potential for withholding errors. Meanwhile, the official assessment system grants full control to the tax authorities, but tends to be less efficient and less actively involves taxpayers. Understanding these three systems is crucial in developing fair and efficient tax policies that can improve compliance and minimize the administrative burden on taxpayers.